Isolation and characterisation of 26 polymorphic microsatellite markers for the parasitoid wasp Trichogramma dendrolimi (Hymenoptera: Trichogrammatidae). Issue 7 (2nd July 2016) - Lü, Xin; Han, Shichou
ABSTRACT: Polymorphic microsatellite markers were developed for the parasitoid wasp Trichogramma dendrolimi . Forty-four microsatellites were isolated from a (TCG)8 -enriched genomic library and characterised. Twenty-six of these loci were polymorphic and could be used for evaluation of the genetic variation of T. dendrolimi .